Harvest dreams of Fr. Mike : coming to fruition - Rodrigo, Michael, d. 1987.; Fernando, Milburga ([Colombo? : s.n.], 1998)
Account of Fr. Michael Rodrigo's experiences at spreading Christianity in Sri Lanka.
Includes bibliographical references.
Keywords: Christianity -- Sri Lanka